Exploring Interpersonal of the Lyrics of “Wildflower” by Billie Eilish - Hasan, Amalia; Silviana, Diah; Ayuningtias, Diah Ikawati (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This study explores interpersonal metafunctions in Billie Eilish’s “Wildflower” using Systemic Functional Linguistics framework, focusing on MOOD and modality patterns. The research analyzes 34 clauses from official lyrics using descriptive qualitative method to understand how interpersonal meaning is constructed. Findings reveal declarative MOOD dominates (88.2%), followed by interrogative MOOD (11.8%), while imperative MOOD is absent. For modality, no modality appears most frequently (44.1%), followed by high modalization (23.5%). Results indicate Eilish uses declarative statements to share personal truths and create intimate connection with listeners, while interrogative moments reveal vulnerability. The prevalence of no modality establishes honest emotional facts, while high modalization provides certainty in uncertain situations. These linguistic choices demonstrate how contemporary artists construct authentic emotional connections through vulnerable yet respectful communication strategies. Keywords: Systemic Functional Linguistics, Interpersonal, Billie Eilish, Wildflower